Negotiating Humanity: A Posthumanist Reading of Ago-ma-ago among Minangkabau Women - Aziz, Abdul; Lita, Ratni Prima; ., Ma’aruf; ., Verinita (Journal of Posthumanism, 2025)
This paper examines the cultural and sociological significance of the Minangkabau women's bargaining behavior known as ago-ma-ago, which transcends transactional economics and serves as a socially embedded practice of negotiation and identity. By employing a qualitative descriptive approach based on in-depth interviews and direct observation in traditional markets in West Sumatra, Indonesia, the study identifies ago-ma-ago not only as a means to obtain better prices but as a dynamic expression of community wisdom, relational identity, and cultural resilience. It reflects emotional intelligence, resistance to capitalist fixed-price norms, and posthumanist values in human interactions. Findings suggest that ago-ma-ago plays a role in maintaining social bonds and informal economic fairness while reaffirming traditional gender roles and cultural knowledge transmission. The paper contributes to broader debates on localized socio-economic agency in the face of modernization and offers a theoretical positioning of ago-ma-ago as an act of cultural preservation and relational negotiation within posthumanist discourses.